Advances in marine structures : proceedings of the 3rd International Conference on Marine Structures–MARSTRUCT 2011, Hamburg, Germany, 28-30 March 2011 /: proceedings of the 3rd International Conference on Marine Structures–MARSTRUCT 2011, Hamburg, Germany, 28-30 March 2011. (©2011) - Unknown
No abstract available